Digital Customs Systems and State Revenue Accountability: A Literature Review on CEISA 4.0 and NLE - Andi Samsu (PT PUSTAKA CENDEKIA GROUP, 2025)
This study examines the role of digital customs systems in strengthening state revenue management with a focus on CEISA 4.0 and the National Logistics Ecosystem. The method used is a qualitative literature study through the synthesis of findings from national and international sources to assess the contribution of digital transformation to public financial management. The results of the study show that digitalization drives service efficiency through process standardization and automation of administrative stages, strengthens supervision through data-based verification and risk assessment support, and increases transparency through audit trails and process traceability. The integration of services and information exchange supported by CEISA 4.0 and the National Logistics Ecosystem strengthens cross-stakeholder coordination, reduces procedural barriers, and improves data consistency that affects the accuracy of levy determination. The study also emphasized that the benefits of accountability are influenced by implementation readiness, including data governance, human resource capacity, inter-agency coordination, and regulatory adjustments. Overall, digital customs systems contribute to a more orderly, transparent, and accountable management of state revenues within the framework of public financial management.